2018
DOI: 10.1186/s12936-018-2554-4
|View full text |Cite
|
Sign up to set email alerts
|

Human mobility and factors associated with malaria importation in Lusaka district, Zambia: a descriptive cross sectional study

Abstract: BackgroundMalaria is a major public health problem in Zambia with an estimated 4 million confirmed cases and 2389 deaths reported in 2015. Efforts to reduce the incidence of malaria are often undermined by a number of factors such as human mobility which may lead to introduction of imported infections. The aim of this study was to establish the burden of malaria attributed to human mobility in Lusaka district and identify factors associated with malaria importation among residents of Lusaka district.MethodsA c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 11 publications
0
14
0
2
Order By: Relevance
“…In adults, behavioural factors including travel, leisure and social activities, and occupational activities such as agriculture or night-time work may have increased the risk of exposure outside the household as compared to children. Travel has been reported as a risk factor for P. falciparum infection in East and Southern Africa [43,44] and for cases of imported malaria being older than those not imported in Southern Africa [45]. Whereas occupational hazards were not evaluated in this study, considerable occupational risk of malaria has been documented among mobile male workers in Asia [46,47] and populations involved in agriculture in Africa [48,49].…”
Section: Discussionmentioning
confidence: 82%
“…In adults, behavioural factors including travel, leisure and social activities, and occupational activities such as agriculture or night-time work may have increased the risk of exposure outside the household as compared to children. Travel has been reported as a risk factor for P. falciparum infection in East and Southern Africa [43,44] and for cases of imported malaria being older than those not imported in Southern Africa [45]. Whereas occupational hazards were not evaluated in this study, considerable occupational risk of malaria has been documented among mobile male workers in Asia [46,47] and populations involved in agriculture in Africa [48,49].…”
Section: Discussionmentioning
confidence: 82%
“…As such, the imported malaria prevalence in this study was lower than most surveys reviewed. The prevalence of imported malaria was higher in most studies; given the 64% in China [ 14 ], about 14 to 90% in Iran [ 33 ], 100% in South Africa [ 34 ], 53% in Swaziland [ 35 ] and 94.2% in Lusaka, Zambia [ 36 ]. However, a study conducted in Botswana showed a lower prevalence of 6.01% [ 37 ], comparable to the findings in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Discussing this study conducted in a moderate malaria transmission zone, in perspective these surveys, makes it clear that imported malaria occurs in low [ 34 , 36 ], high [ 34 ] as well as moderate transmission zones, in varying proportions and without a pattern specific for particular zones. For a long time now the World Health Organization (WHO), has been recommending quantifying of the importation of infections into a region [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other factors that were not associated with LLIN use during travel included time to bed, gender of the participant, and age at the time of travel. Travel has been identi ed as a risk factor for malaria across Africa [11,15,19,30,31]. In Uganda, a study conducted at three sites of varied malaria transmission demonstrated that the incidence of malaria in travellers was over three times higher in the 60 days after overnight travel compared to the 60 days before travelling [16].…”
Section: Discussionmentioning
confidence: 99%
“…Travel is a well-recognised risk factor for malaria [10][11][12][13][14][15]. Studies from Uganda and elsewhere in Africa have shown that overnight travel is associated with an increased risk of malaria, especially when individuals travel from areas of lower transmission intensity to higher risk areas [16,17].…”
Section: Introductionmentioning
confidence: 99%